2017
DOI: 10.47197/retos.v0i33.49638
|View full text |Cite
|
Sign up to set email alerts
|

Programa de actividad física y su incidencia en la depresión y bienestar subjetivo de adultos mayores (Impact of a physical activity program on older adults’ depression and subjective well-being)

Abstract: El artículo se enfoca en el análisis de un programa de actividades físicas y su efecto en la mejora de los niveles de depresión y bienestar subjetivo de adultos mayores. Se utiliza un diseño experimental con pre y pos tratamiento en una muestra de 111 adultos mayores seleccionado mediante criterios de inclusión, a la que se le aplicó un procedimiento de proporción de uno a tres para crear el grupo experimental y de control (n=74 grupo experimental y n=37 el grupo de control). La depresión fue medida aplicando … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
2
Order By: Relevance
“…Thus, although exercise may be used excessively and compulsively by women with eating disorders, the practice with adequate supervision can improve aspects related to the disorder. Therefore, it is interesting that college students are guided on the importance of physical exercise, not only for the health benefits, like reducing the prevalence of overweight and obesity (Chávez Valenzuela et al, 2018), improvement of physical fitness (Bahamonde et al, 2019), improvement in levels of depression and subjective well-being (Guillen Pereira et al, 2018), improved self-esteem (García González & Froment, 2018), but also for the positive impact that it can bring on disordered eating attitudes and behaviors. The last variable included in the model, as a predictor of disordered eating attitudes and behaviors, was the general attractiveness ideal internalization, corroborating results of previous studies (Izydorczyk & Sitnik-Warchulska, 2018;Hosseini, et al, 2016;Vartanian & Hopkinson, 2010;Argyrides, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although exercise may be used excessively and compulsively by women with eating disorders, the practice with adequate supervision can improve aspects related to the disorder. Therefore, it is interesting that college students are guided on the importance of physical exercise, not only for the health benefits, like reducing the prevalence of overweight and obesity (Chávez Valenzuela et al, 2018), improvement of physical fitness (Bahamonde et al, 2019), improvement in levels of depression and subjective well-being (Guillen Pereira et al, 2018), improved self-esteem (García González & Froment, 2018), but also for the positive impact that it can bring on disordered eating attitudes and behaviors. The last variable included in the model, as a predictor of disordered eating attitudes and behaviors, was the general attractiveness ideal internalization, corroborating results of previous studies (Izydorczyk & Sitnik-Warchulska, 2018;Hosseini, et al, 2016;Vartanian & Hopkinson, 2010;Argyrides, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We consider that the identification of osteoarticular disease predictors, such as poor physical performance, is essential for the early identification of people at risk, as Veronese et al [7] confirmed during a four-year study of an elderly group. Scientific literature has shown sufficient evidence to support the use of exercise in preventive treatment of depression, anxiety, and stress [7,18,[24][25][26]50,51]. A recent study carried out during COVID-19 confinement has underscored the relationship between a reduction in physical activity levels and social distancing, worsening the mental health of the elderly and especially those who are less functional [52].…”
Section: Discussionmentioning
confidence: 99%
“…It has been effective in reducing depressive symptoms and even as an alternative to medication [23]. Salguero et al [18] suggested that physical activity can be effective in alleviating depressive symptoms, and recent research has demonstrated the beneficial effects of programmed physical exercise in reducing depression [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Los beneficios del ejercicio en diferentes ámbitos del bienestar psicológico son reconocidos como un aporte relevante para la calidad de vida (Astorga, González, Martínez, Rojas & Borges, 2021) y la salud mental de cada individuo, promoviendo el bienestar emocional y contribuyendo a disminuir síntomas relacionados al trastorno depresivo (Murri et al, 2018). Asimismo, el ejercicio promueve efectos positivos en población adulta y adulta mayor sobre los síntomas depresivos, la autoestima, la ansiedad y la calidad de vida, el cual permite usar recursos para enfrentar los factores estresantes, disminuyendo estos a un nivel significativo (Araque-Martínez, Ruiz-Montero & Artés-Rodríguez, 2021;Guillén, Bueno, Gutiérrez & Guerra, 2018;Kekäläinen, Kokko, Sipilä, & Walker, 2018). Por otra parte, las actividades lúdicas (juegos tradicionales) actúan como un factor que canaliza la ansiedad y la tensión tanto en adolescentes como en adultos (Nisha & Umarani, 2013).…”
Section: Introductionunclassified